Cationic Supramolecular Vesicular Aggregates for Pulmonary Tissue Selective Delivery in Anticancer Therapy. (8th March 2016) - Licciardi, Mariano; Paolino, Donatella; Mauro, Nicolò; Cosco, Donato; Giammona, Gaetano; Fresta, Massimo; Cavallaro, Gennara; Celia, Christian
Abstract: The biopharmaceutical properties of supramolecular vesicular aggregates (SVAs) were characterized with regard to their physicochemical features and compared with cationic liposomes (CLs). Neutral and cationic SVAs were synthesized using two different copolymers of poly(aspartyl hydrazide) by thin‐layer evaporation and extrusion techniques. Both copolymers were self‐assembled in pre‐formulated liposomes and formed neutral and cationic SVAs. Gemcitabine hydrochloride (GEM) was used as an anticancer drug and loaded by a pH gradient remote loading procedure, which significantly increased drug loading inside the SVAs. The resulting average size of the SVAs was 100 nm. The anticancer activity of GEM‐loaded neutral and cationic SVAs was tested in human alveolar basal epithelial (A549) and colorectal cancer (CaCo‐2) cells. GEM‐loaded cationic SVAs increased the anticancer activity in A549 and CaCo‐2 cells relative to free drug, neutral SVAs, and CLs. In vivo biodistribution in Wistar rats showed that cationic SVAs accumulate at higher concentrations in lung tissue than neutral SVAs and CLs. Cationic SVAs may therefore serve as an innovative future therapy for pulmonary carcinoma. Abstract : What a GEM : Gemcitabine hydrochloride (GEM) was trapped in cationic supramolecular vesicular aggregates (SVAs) using a pH gradient remote loading procedure, increasing the amount of precipitated GEM inside the aqueous compartment. The GEM‐loaded SVAs were found to target lung tissues selectively, with decreased anticancer activity in both A549 and CaCo‐2 cells, and pulmonary tissue showing a different response before and after treatment.